The Catalogue of Stellar Parameters from the Detached Double-Lined Eclipsing Binaries in the Milky Way. (2nd May 2014) - Eker, Z.; Bilir, S.; Soydugan, F.; Gökçe, E. Yaz; Soydugan, E.; Tüysüz, M.; Şenyüz, T.; Demircan, O.
Abstract: The most accurate stellar astrophysical parameters were collected from the solutions of the light and the radial velocity curves of 257 detached double-lined eclipsing binaries in the Milky Way. The catalogue contains masses, radii, surface gravities, effective temperatures, luminosities, projected rotational velocities of the component stars, and the orbital parameters. The number of stars with accurate parameters increased 67% in comparison to the most recent similar collection by Torres, Andersen, & Giménez (2010). Distributions of some basic parameters were investigated. The ranges of effective temperatures, masses, and radii are 2 750<T_eff (K) < 43000, 0.18 < M / M ⊙ < 33, and 0.2 < R / R ⊙ < 21.2, respectively. Being mostly located in one kpc in the Solar neighborhood, the present sample covers distances up to 4.6 kpc within the two local Galactic arms, Carina-Sagittarius and Orion Spur. The number of stars with both mass and radius measurements better than 1% uncertainty is 93, better than 3% uncertainty is 311, and better than 5% uncertainty is 388. It is estimated from the Roche lobe filling factors that 455 stars (88.5% of the sample) are spherical within 1% of uncertainty.